Gene flow and selection evidence of sandalwood (Santalum album) under various population structures in Gunung Sewu (Java, Indonesia), and its effects on genetic differentiation - YENI W.N. RATNANINGRUM; SAPTO INDRIOKO; ENY FARIDAH; ATUS SYAHBUDIN (Society for Indonesian Biodiversity, 2017)
Ratnaningrum YWN, Indrioko S, Faridah E, Syahbudin A. 2017. Gene flow and selection evidence of sandalwood (Santalum album) under various population structures in Gunung Sewu (Java, Indonesia), and its effects on genetic differentiation. Biodiversitas 18: 1493-1505. Field observations on population structures and isoenzyme analysis were conducted to determine gene flow and selection evidence of sandalwood under various population structures in Gunung Sewu, and its effects on genetic differentiation. Sandalwood (Santalum album Linn., Santalaceae) is origin to the south-eastern islands but recently emerged as new landraces in Java Island, Indonesia. Results suggested that (i) natural barriers contributed to habitat fragmentation and disrupted gene flow among populations; (ii) gene flow affected selection processes regarding bottleneck effects and genetic drifts, which determined allelic richness and population diversity; and (iii) variation on gene flow and selection processes affected genetic differentiation among populations. Gene flow restriction and genetic drift occurred when population had lower genetic base, highly clonalized, fragmented, and/or more inbreeding in mating. Genetic differentiation was highest between populations within Timor island, and between Gunung Sewu (Java Island) and Sumba-Timor islands. Populations were not clustered based on geographical sites, but more by the similarity of genetic structures. Genetic differentiations were the combined effect of the differences on genetical processes regarding gene flow and selection events. Both differences existed due to differences on (i) population structures including landscape, clonality and parental genetic composition, and (ii) the disturbance histories of population, which affected the equilibrium between gene flow and drift. These findings emphasized the importance of larger gene flow and genetic base to naturally maintain genetical processes of sandalwood population under various landscapes structures.